Religiosity, Islamic Lifestyle, and the Adoption of Edutainment Television Among Muslim Viewers: An Extended Technology Acceptance Model - Fatmawati Fatmawati; Ade Sofyan Mulazid; Armawati Arbi; Kalsum Minangsih (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2026)
This study examines the factors that influence the intention and actual behavior of Muslim viewers in watching edutainment television. It applies an extended Technology Acceptance Model (TAM) in which religiosity serves both as a direct predictor and as a moderator of the link between intention and behavior. Survey data were collected from 216 Muslim respondents in the Jakarta metropolitan. The data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that religiosity significantly predicts the intention to watch and actual viewing of edutainment television. Behavioral intention is the strongest predictor of actual viewing. Religiosity also positively moderates the relationship between intention and actual viewing. The study implies that value-based constructs must be incorporated into TAM when the object of adoption is religiously meaningful content, and that religiosity serves as a bridging mechanism in the intention-to-behavior relationship rather than merely as an additional antecedent. The study is limited by a purposive sample drawn from a single metropolitan region and by a cross-sectional, self-reported design.